Size matters: narratives of men who have been amputaded as a result of penile cancer (Research, Society and Development, 2021)
Objective: The present research is aimed at discussing the reasons behind patients’ delayed initiative in seeking healthcare assistance for penile cancer. It was established as secondary objectives to list subjective factors that influence the delayed initiative in accessing SUS (Brazil’s public healthcare system) for the diagnosis of penile cancer, to analyze individual and collective cultural factors leading to the image construction of the man with penile cancer. Method: It was a qualitative, descriptive, exploratory, analytical research with fourteen interviewees, using thematic analysis as well as the support of the theory of social representations. Results:  The study was comprised of young adults and men who are in their sixties, aged 35 to 70, diagnosed with penile cancer, most interviewees attended only incomplete elementary school and are Catholics, with a monthly income around one or two minimum wages. We produced two categories of analysis that cover different temporalities of the disease. The first one regarding the moment prior to the diagnosis of penile cancer, which we have named as a “pimple in nature”; “Does size matter”? referring to the period after cancer has been diagnosed. Final Considerations: We can state after hearing the interviewees that the fundamental idea about penile cancer and the amputation surgery is the fear of losing size, thus having a smaller.